Applying Metacognitive Strategies in Community Nursing Education: A BOPPPS Model Approach - Cheng Cheng (Nursing Education Perspectives, 2026)
This study evaluated the use of a metacognitive-based program integrated with the BOPPS model (Bridge-in, Objective, Preassessment, Participatory Learning, Postassessment, and Summary) in a sample of 78 third-year nursing students. Metacognitive awareness (monitoring, evaluation, and regulation) was assessed using the Metacognitive Awareness Inventory before and after the course; reflective essays captured learning experiences. Paired-sample t tests and thematic analysis revealed significant gains in monitoring and regulation but not evaluation. Students reported greater learning initiative, a deeper understanding of community nursing, and improved teamwork and problem-solving skills. Integrating metacognitive strategies within the BOPPS model offered an effective approach to fostering professional competence in nursing education.